The need to develop creative labor market behavior - Csehné Papp, Imola (Studia Mundi – Economica, 2015)
The study explains the Hungarian students awareness of the labour market. I assume that today ’s information society is open to all possibilities, which increases the adaptability of the labor market, thereby reducing anomalies between the education and labor market demands as well as among the regional differences. The test method was the questionnaire. The hypothesis has been proved only partly. Thetest resultsshowed that in the whole country we shouldplay a greater rolein order to offer information for workers about the labor market.